2002
DOI: 10.1136/bjo.86.11.1262
|View full text |Cite
|
Sign up to set email alerts
|

Relation between perceived driving disability and scores of vision screening tests

Abstract: Aim: To determine the relation between perceived driving disability and vision screening tests. Methods: 93 subjects, aged 50 years and over, with binocular visual acuity of at least 20/80. Perceived driving disability (PDD) was assessed by a questionnaire. Subtracting daytime from night-time driving question scores revealed PDD at night (PDDN), subtracting scores of questions for driving in familiar places from those in unfamiliar places revealed PDD at unfamiliar places (PDDU). Results: PDD was strongly rela… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
27
0
2

Year Published

2004
2004
2013
2013

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(33 citation statements)
references
References 9 publications
4
27
0
2
Order By: Relevance
“…While visual acuity has traditionally been seen as the cornerstone of ophthalmologic care and visual function, the role of glare and contrast sensitivity has recently gained importance when assessing the quality of vision [1]. Consideration of these additional parameters has become particularly important in cataract and refractive surgery, where restoration of excellent visual acuity may not necessarily lead to complete patient satisfaction if the vision is tinged by troublesome glare [1].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…While visual acuity has traditionally been seen as the cornerstone of ophthalmologic care and visual function, the role of glare and contrast sensitivity has recently gained importance when assessing the quality of vision [1]. Consideration of these additional parameters has become particularly important in cataract and refractive surgery, where restoration of excellent visual acuity may not necessarily lead to complete patient satisfaction if the vision is tinged by troublesome glare [1].…”
Section: Introductionmentioning
confidence: 99%
“…Consideration of these additional parameters has become particularly important in cataract and refractive surgery, where restoration of excellent visual acuity may not necessarily lead to complete patient satisfaction if the vision is tinged by troublesome glare [1].…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, a previous study only revealed a weak relationship between glare tests and (self) perceived driving disability. 17 This suggested that there is a discrepancy between perceived and true disability; that is, that people may not be aware of their impairment. This fact adds to the importance of glare testing for driver license applications.…”
Section: Introductionmentioning
confidence: 99%
“…Zmiana subiektywnie postrzeganej jasności i szybkości ruchu tak samo jasnych powierzchni powoduje, że kierowcy inaczej oszacowują odległość i prędkość niż podczas dnia, co staje się przyczyną wielu kolizji (22).…”
Section: Czynniki Wewnętrzneunclassified